Compuparts Game Development as Interactive Learning Media About Computer Components Using GDLC Method - Rahmat Hidayat; Rahmad Al-Rian; Pratama Benny Herlandy; Melly Novalia (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This research develops CompuParts Game, a mobile-based educational game that serves as an interactive learning media to understand computer components. The game was designed using the Game Development Life Cycle (GDLC) method which consists of six main stages, namely concept design, pre-production, production, testing, launch, and post-production. By applying gamification principles, the game features levels, leaderboards, and immediate feedback to increase user engagement in the learning process. Evaluation was conducted on 20 students, with the results showing that the game is effective in improving the understanding of the function and assembly of computer components in a more interactive and fun way. In addition, the questionnaire results showed a user satisfaction level of 85.75%, which indicates that this game is well received as a mobile-based learning media. The use of CompuParts Game is expected to be an innovative solution in improving the accessibility and effectiveness of technology learning, especially in the growing digital education environment. With an interactive approach, this game provides a more interesting learning experience and motivates students to better understand technology concepts in depth.